Dominasi Kekuatan Ekonomi dalam Pilkades Kabupaten Toba Samosir Tahun 2010 - N.YUNIOR F. H HUTAPEA (Politeia: Jurnal Ilmu Politik, 2017)
The democratic system is inseparable from the existence of the elite.Elite has an important role in democracy as a group that can affect people in politics. Dominated by economic elites have occurred in election of the Kepala Desa Simare in Toba Samosir regency in 2010. This study found there arethree interesting phenomenonrelating to the economic elite. First, there are resources in the form of wealth for political power; Second, the economic elite were able to control the villagers Simare; Third, the economic elites dominate Simare village government structure.Elite has initiated expansion Simare village is economic elite. They have a wealth of economically. With a wealth of resources possessed by the economic elites make it easier to gain political power in the sense of forming a government village.The study used the approach to political ideology. This study method is descriptive. Collecting data with depth interview. Analysis of data using qualitative analysis. Keywords: Domination, economic elite, village government.